The role of the positive personality traits of the physical education and sports teacher in reducing school violence among secondary school students - MOKRANE, Khaled; ABBACHE , Ayoub (sports creativity, 2023)
The research aims to identify the role of the positive personality traits of the personality of the teacher of physical education and sports in reducing school violence among secondary school students, and the importance of the research lies in addressing the phenomenon of violence in the school, in this study the researcher adopted the descriptive approach and used the questionnaire to collect information’s, was applied to a sample of 56 teachers in secondary schools in the eastern province of Algiers, , it was concluded that positive traits of the personality have a major role in reducing school violence among secondary school students.